A comprehensive review on combustion stabilization technologies of micro/meso-scale combustors for micro thermophotovoltaic systems: Thermal, emission, and energy conversion. (1st March 2023) - Cai, Lei; E, Jiaqiang; Li, Jintao; Ding, Jiangjun; Luo, Bo
Highlights: Combustion stabilization technologies for micro/meso-scale combustors are reviewed. Flammable range is expanded by applying combustion stabilization technology. Combustion stabilization technology improves outer wall temperature distribution. Combustion stabilization technology effectively reduces pollutant emissions. Combustion stabilization technology improves energy conversion efficiency. Abstract: Owing to its high energy density, the combustion-based micro thermophotovoltaic system has promising prospects and becomes the most potential substitute for conventional power generation systems. As one of the most critical components in micro thermophotovoltaic systems, however, micro/meso-scale combustors are still confronted with many challenges due to the scale effect. Therefore, it is of great significance to develop combustion stabilization technologies for micro/meso-scale combustors. During the past two decades, many researchers have proposed various combustion stabilization technologies, which have been reviewed in this work. According to the working principle, different micro/meso-scale combustion stabilization technologies can be classified into three categories: heat recirculation, flow recirculation, and combustion optimization. The results indicate that these technologies can effectively expand the flammable range and have a positive effect on the stable combustion in micro/meso-scale combustors. Furthermore, the working performance of micro/meso-scale combustors, including thermal performance, emission performance, and energy conversion performance, has been evaluated. The results demonstrate that the application of different combustion stabilization technologies to micro/meso-scale combustors effectively increases the outer wall temperature distribution, reduces CO/NOX emissions, and improves the combustion/radiation efficiency. Finally, the challenges and prospects of future work are outlined. This work expounds on the research progress of micro/meso-scale combustors for micro thermophotovoltaic systems, which provides references for subsequent research and applications.